Please multiply ( x + 4) * (x + 6)
Before solving the problem we should understand how to approach multiplying binomials. There is a term called FOIL, which stands for F = first, O = outer, I = inner, and L = last. (x + 4) * (x + 6) F: multiplying the first terms we would get x * x = x^2 O: multiplying the outer terms we would get x * 6 = 6x I: multiplying the inner terms we would get 4 * x = 4x L: multiplying the last terms we would get 4 * 6 = 24 Now when we combine everything we would get: x^2 + 6x + 4x + 24 Then we can simplify like terms to get: x^2 + 10x + 24
We are to receive $200 at the end of 4 years. How do we calculate the present value of the amount, assuming the interest rate is 10% per year compounded annually?
First, we want to identify the present value formula we will be using to solve this problem. PV = FV x [ 1 / (1 + i)^n] PV = Present Value FV = Future Value i = Interest n = Number of years Second, based on the problem we will identify the values we know. PV = ?, what we are solving for FV = $200 i = 10% n = 4 Third, we will plug in these values into the equation. PV = $200 x [ 1 / (1+.10)^4] PV = $200 x [ 1 / (1.10)^4] Add the denominator prior to raising it to its power PV = $200 x [ 1 / (1.4641)] Then take 1.10 and raise it to the fourth power PV = $200 x [.68301] Then divide 1 by 1.4641 PV = $136.60 Then multiply 200 by .68301 The present value is $136.60, meaning that if we receive $200 in 4 years with an interest of 10% compounded annually, it is the same as receiving $136.60 today.
Simplify the expression 3x^2 + 2x(6x - 4)
3x^2 + 2x(6x - 4) Use distributed property: = 3x^2 + 2x(6x) + 2x(-4) Multiply and clear the parentheses. = 3x^2 + 12x^2 - 8x Combine like terms by adding the coefficients. = 15x^2 - 8x